Assessing quality of life in childhood cancer survivors at risk for hearing loss: a comparison of HEAR-QL and PROMIS measures - Spence, Anne; L’Hotta, Allison J.; Hayashi, Susan S.; Felts, Kara; LaFentres, Emily; Jones-White, Megan; Lieu, Judith E. C.; King, Allison A.; Hayashi, Robert J. (Frontiers in Oncology, 2024)
Background: Childhood cancer survivors (CCS) exposed to platinum chemotherapy are at an increased risk of developing hearing loss and reporting decreased quality of life (QOL). This study compared two QOL measures; one developed for children with hearing loss, The Hearing Environments and Refection on Quality of Life (HEAR-QL), and one validated in CCS, the Patient-Reported Outcomes Measurement Information System (PROMIS), to assess their ability to evaluate QOL deficits in this population. Methods: Subject eligibility were restricted to CCS exposed to platinum-based chemotherapy but who were free of known risk factors for cognitive impairment, (non-central nervous system tumor, no cranial radiation, or intrathecal chemotherapy). Participants had to be between 8-17 years, have completed anti-cancer therapy for at least 6 months, and have an audiogram within 1 year, Participants completed the HEAR-QL-26 (7-12 years) or the HEAR-QL-28 (13-18 years) and the PROMIS. Independent samples and/or one sample T-tests were utilized to compare participants with normal hearing and hearing loss, and to compare outcome measures to normative HEAR-QL and PROMIS data. Non-parametric correlations were utilized to evaluate the relationship between QOL and demographic and medical variables, and QOL and severity of hearing loss. Results: Fifty-four CCS were evaluable. The mean age was 12.0 years. Twenty-eight participants (51.9%) received cisplatin, 30 (55.6%) carboplatin, and 4 (7.4%) received both. Twenty participants (37%) demonstrated hearing loss. Participants with hearing loss scored significantly lower on the